On the Use of Current or Forward-Looking Data in Monetary Policy: A Behavioural Macroeconomic Approach - Paul De Grauwe; Yuemei Ji (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyse the use of current and forward-looking data in the setting of monetary policy (Taylor rule). We answer the question of whether the use of forward-looking data is to be preferred over the use of current data. We use a behavioural macroeconomic model that generates periods of tranquillity alternating with crisis periods characterized by fat tails in the distribution of output gap. We find that the answer to our question depends on the nature of the monetary policy regime. In general, in a strict inflation targeting regime the use of forward-looking data leads to a lower quality of monetary policymaking than in a dual mandate monetary policy regime. Finally, nowcasting tends to improve the quality of monetary policy especially in a strict inflation targeting regime.
Keywords: 330; Taylor rule; behavioural macroeconomics; animal spirits; strict inflation targeting; dual mandate; nowcasting